Reliability–redundancy allocation problem considering optimal redundancy strategy using parallel genetic algorithm - Kim, Heungseob; Kim, Pansoo (Reliability engineering & system safety, 2017)
To maximize the reliability of a system, the traditional reliability–redundancy allocation problem (RRAP) determines the component reliability and level of redundancy for each subsystem. This paper proposes an advanced RRAP that also considers the optimal redundancy strategy, either active or cold standby. In addition, new examples are presented for it. Furthermore, the exact reliability function for a cold standby redundant subsystem with an imperfect detector/switch is suggested, and is expected to replace the previous approximating model that has been used in most related studies. A parallel genetic algorithm for solving the RRAP as a mixed-integer nonlinear programming model is presented, and its performance is compared with those of previous studies by using numerical examples on three benchmark problems. •Optimal strategy is proposed to solve reliability redundancy allocation problem.•The redundancy strategy uses parallel genetic algorithm.•Improved reliability function for a cold standby subsystem is suggested.•Proposed redundancy strategy enhances the system reliability.